Field choice in spring and breeding performance of Greylag Geese Anser anser in southern Sweden. - Nilsson, L; Green, M; Persson, H (Wildfowl, 2014)
Selection and exploitation of feeding areas by pre-breeding and nonbreeding Greylag Geese A nser anser, as we ll as by families, was studied in a breeding area consisting of four lakes in Scania, southernmost Sweden, in the years 1997-2000. Total production of young in each lake as we ll as the breeding performance of neck collared individuals was established annually, 1985-2000. This breeding population increased on average 15.3% p e ra n n um, from 93 pairs in 1985 to 910 pairs in 2001. The two main field types used by pre-breeding pairs, males of incubating females and non-breeders in flocks were win te r wheat and grassland, often switching from the former to the latter in mid-season. Almost all feeding during brood- rearing took place on pastures grazed by livestock or on a golf-course. Generally in spring, the rates of exploitation were below 300-400 goose days ha"1, but rates of >1,000 goose days ha' 1 were noted for one cereal field and two grassland areas. The rates of exploitation by families varied markedly among brood-rearing areas as we ll as years, being highest all through the study period on a grazed pasture, where it ranged 800-1,350 goose days ha'1. Including the utilisation by non-breeders, the annual exploitation of this pasture ranged from 1,400 to 2,500 goose days h a 1. At the only lake without grazing by livestock (since the mid-1990s), significantly fewer goslings survived to fledging than at the other lakes (45% vs 70%). Indications of density-dependent effects on the productivity of small young were noted at one of the lakes (Klosterviken) but not at another (Yddingen). Most likely, the lack of any density dependent effect, in spite of the very marked increase in the breeding population during the study period at Yddingen, is the result of access to highly fertilized grass on a golf course.